Analisis Produksi Dan Ketersediaan Serta Kebutuhan Kedelai Dalam Kaitannya Dengan Ketahanan Pangan Di Provinsi Sumatera Utara - Cut Nasmiati; Rahmanta Ginting; Abdul Rahman (JURNAL AGRICA, 2018)
This research aims to describe production development, avaliability and demand of soybean in North Sumatra Province in 2002-2013 as well as forecast production progress and avaliability in relation to food security in North Sumatra Province in 2014-2020 using various forecasting methods. The result showed fluctuate production development during 2002-2013, which sharply descended in 2013. The development of soybean's avalibility in 2002-2013 increased annually due to the role of imports, done in order to meet soybean needs in the province. The development of soybean demands for 2002-2013 also showed increasing trend to due to population growth and increasing soybean consumption per capita per year. Therefore, if import is not implemented then the regional soybean production can not meet soybean needs for consumption and agro-industries such as livestock feed and seeds. Soybean production forecast for 2014-2020 is estimated to be remain low, stable and incapable to fulfill basic soybean needs in the province if basic improvement measures are not implemented. Avaliablity prediction for 2014-2020 also leads to ascending pattern which caused by mutually increasing avaliability of imported soybean. Prediction for 2014-2020 needs will also increase in tow with the growth of population. In addition to production and productivity accession efforts, the author also suggests that data collecting, as well as more detailed forecasts of soybean production, avaliability and needs are highly iwportant to the government in order to fulfill food needs of society. There must be be biodiversity and food consumption variety in order to lessen soybean demands (specifically the imported ones), attempts to raise farmer's interest in planting soybean and stake holders role expansion, not only to manifest food security but also achieve food suffiency. Keywords : Production, availiability, impor, demand, food security.